The Use of Botulinum Toxin in the Treatment of Headache: an Integrative Literature Review - Falcão, Stephanie Bezerra Muniz; Brito, Pedro Serra Galdino Farias de; Oliveira, Ellenicy Barbosa; Rodrigues, Ana Beatriz Rocha; Sales, Mariana Luna de; Diniz, Maria Eduarda Santos; Farias, Ítalo de Lima; Silva, Ismael Lima; Alencar, Layla Beatriz Barroso de; Andrade, Arthur Marques de; Sá, Joyce Raianne Santos; Oliveira, Wictoria Gabrielle Lima de; et al. (Headache Medicine, 2023)
Full abstract in PDF.